Use of adhesively inserted full-ceramic restorations in the conservative treatment of amelogenesis imperfecta: A case report - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2003)
Amelogenesis imperfecta is an inherited disorder that presents a major challenge to the dentist for prosthetic treatment of missing and/or malformed tooth structures. This clinical report presents the use and short-term clinical performance of adhesively-inserted full-ceramic restorations in the restoration of a case of amelogenesis imperfecta.
Keywords: CLINICAL-EVALUATION; BOND STRENGTHS; SYSTEMS; ENAMEL; INLAYS